First Isolation, Molecular Identification, and Phylogenetic Characterization of A3B5 Very Virulent Infectious Bursal Disease Virus in Pullets in Chile - Leandro Cádiz; Miguel Guzmán; Paola Rivera; Fernando Navarrete; Paulina Torres; Héctor Hidalgo (Microbiology Research)
Infectious bursal disease virus (IBDV) is an important pathogen affecting the poultry industry worldwide. IBDV serotype 1, including classical virulent strains (cvIBDV), variant strains (varIBDV), and very virulent strains (vvIBDV), is pathogenic for chickens. IBDV mainly infects immature B-lymphocytes in the bursa of Fabricius, weakening the humoral immune response and leading to secondary infections and increased morbidity and mortality. The Laboratory of Avian Pathology received ten live 8-week-old pullets from a laying hen operation experiencing increased mortality, prostration, diarrhea, and sudden death. Upon necropsy, the affected birds presented swollen, hemorrhagic, and edematous bursa of Fabricius, as well as hemorrhage in the breast and thigh muscles. RT-PCR confirmed that the samples from the bursa of Fabricius were positive for IBDV. Phylogenetic analysis of the VP1 and VP2 gene nucleotide sequences classified the strain, isolated in embryonated chicken eggs, as the A3B5 genotype. Amino acid sequence analysis of the VP2 hypervariable region revealed the presence of amino acid residues commonly found in vvIBDV. Additional studies are required to investigate the epidemiological situation of this genotype in Chile and to evaluate current vaccination plans and their effectiveness against new variants.